Withdrawing Drugs in the U.S. Versus Other Countries - Benson Ninan; Albert I Wertheimer (INNOVATIONS in Pharmacy, 2012)
Since 1979, the United Nations has maintained a list of drugs banned from sale in member countries. Interestingly, there are a number of pharmaceuticals on the market in the USA that have been banned elsewhere and similarly, there are some drug products that have been banned in the United States, but remain on the market in other countries. This report provides a look into the policies for banning drug sales internationally and the role of the United Nations in maintaining the master list for companies and countries to use for local decision guidance.